The Impact of Preprocessing on Classification Performance in Convolutional Neural Networks for Turkish Text - Salur, Mehmet Umut; Aydin, Ilhan (Ieee, 2018)
The increase of text based content produced in electronic environment necessitated to classify these contents with advanced algorithms. For text classification, the text contents are reduced to a more structured form by being preprocessed. Many studies have examined how these preprocesses affect the performance of classification algorithms. The main question of this study is how the Convolutional Neural Network (CNN), which is noteworthy with its classification success, is influenced by text preprocessing in the text classification. In this study, the effect of text preprocessing is examined CNN classification performance on two different data sets with Turkish content. As a result of the study, it has been determined that the text preprocessing has a weak positive effect on CNN classification performance.
Türkçe Metin Siniflandirmada Metin önişlemlerinEvrişimsel Yapay Sinir A?i Siniflandirma Başarimi üzerindeki Etkisi
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Text Classification; Convolutional Neural Networks; Text Preprocessing